REVEALING ELECTROMIGRATION ON DIELECTRICS AND METALS THROUGH THE STEP-BUNCHING INSTABILITY - Usov, Victor; Ó Coileáin, Cormac; Chaika, Alexander N.; Bozhko, Sergey I.; Semenov, Valery N.; Krasnikov, Sergey; Toktarbaiuly, Olzat; Stoyanov, Stoyan; Shvets, Igor V. (PHYSICAL REVIEW B, 2020)
Electromigration, due to its technological and scientific significance, has been a subject of extensive studies for many years. We present evidence of electromigration in dielectric materials, namely C -plane sapphire, obtained from direct experimental observation of an atomic step-bunching instability driven by electromigration. We further expand upon our previously reported findings of electromigration induced step-bunching transformation of a metal surface. The only system where electromigration driven step bunching has been observed and comprehensively investigated is the low index surfaces of silicon. In this study we show that electromigration driven SB can be induced on a variety of crystallographic surfaces, including metals and insulating oxides, and may be more prevalent than previously thought. Electric fields were applied at high temperature to W(110) and A l 2 O 3 ( 0001 ) crystals whereupon their surface reordered to a morphology closely resembling that of Si(111) with atomic steps bunched by electromigration. This suggests that the mechanism of step bunching on the W(110), A l 2 O 3 ( 0001 ) , and Si(111) can be fundamentally the same. Annealing W(110) offcut in the [001] direction with an up-step current produced a morphology with the bunch edges composed of zigzag segments meeting at a right angle.
Keywords: Type of access: Open Access; electromigration; dielectrics; metal; step-bunching instability